PERGESERAN NILAI KEAGAMAAN DAN SOSIAL BUDAYA MASYARAKAT PETANI (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2002)
The modernization of agricultural technology in villages promises effectivity, efficiency, and maximum result in agricultural sector that Indonesia was able to be self-sufficient in rice in 1984. it also causes many significant shifts and changes in the aspect of farmer community's value and behavior. The shifts and changes, predictably, will result in a new problem that will replace, even completely remove, religious and traditional socio-culltural value and behavior. Those value and behavior have positive as well as negative impact for society and agricultural development.